Long-term response of groundcover components to organic and conventional weed control in shaded and open-sun coffee in Nicaragua. (July 2020) - Staver, C.; Juventia, S.; Navarrete, E.; Navarrete, L.; Sepulveda, N.; Barrios, M.
Abstract: The weed-free period is employed to evaluate the effectiveness of practices to reduce crop loss to weeds. To orient sustainable cropping system approaches in perennial crops such as coffee which are often grown with trees, orchard floor or groundcover management has been proposed to address not only crop loss, but also soil protection, plant nutrition, habitat for beneficial organisms and labor and input costs. The results of a long-term experiment in Masatepe, Nicaragua, comparing two intensities of organic and conventional coffee management under four combinations of deciduous and evergreen trees either leguminous ( Inga laurina and Samanea saman ) and non-leguminous ( Simarouba glauca and Tabebuia rosea ) and full sun concluded that with selective weed management under trees, soil is protected with both low-growing, shallow-rooted cover vegetation and tree leaf litter without yield loss, while also reducing herbicide and labor use. Over 11 years, treatments with trees compared to full sun coffee showed near absence of bare soil (P < .001) and increasing presence of leaf litter (P < .001) and cover vegetation (P < .001), especially in the first 8 years. Selective control, either herbicide or manual, resulted in minimal bare soil, a declining area covered by weeds and increased area, from 40 to 70%, under cover vegetation. Selective control with herbicides had less weedy vegetation than manual selective control. Trees compared to full sun showed increased accumulation of whole leaf and fractionated leaf layers measured in the dry season with treatments including Inga laurina greater than other tree treatments. Labor and herbicide costs declined with increasing time under trees (P < .001), while selective control reduced herbicide use with higher labor costs. A regression of groundcover components on coffee berry yields explained less than 10% of variability. Two research priorities are identified to increase the contribution of groundcover components to sustainable coffee systems – 1) cover vegetation species and management in water conservation and use and 2) the role of tree species and their litter on water, soil biology dynamics and O horizon formation. Highlights: Leaf litter increased with tree age with significant species differences. Selective management shifted weed composition to low-growing, shallow-rooted species. Bare soil declined with tree presence and selective management. Tree presence, field age and selective practices reduced herbicide and labor use. Coffee yields were not linked to amounts or presence of living vegetation or litter.